2011
DOI: 10.1097/nen.0b013e3182270f8e
|View full text |Cite
|
Sign up to set email alerts
|

Prominent Microglial Activation in the Early Proinflammatory Immune Response in Naturally Occurring Canine Spinal Cord Injury

Abstract: Better understanding of the pathogenesis of spinal cord injury (SCI) is needed for the development of new therapeutic strategies. Spinal cord injury has been investigated in various rodent models, but extrapolation to humans requires the use of a large animal model that more closely mimics human SCI. Dogs frequently develop spontaneous SCI with features that bear a striking resemblance to the human counterpart. We investigated the temporal course of the immune response during naturally occurring canine SCI and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
100
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(104 citation statements)
references
References 91 publications
2
100
2
Order By: Relevance
“…In a previous study that examined mRNA expression of cytokines in the spinal cord of dogs with IVDH-associated SCI, IL-8 was likewise found to be increased, compared to control dogs, especially in acute injury. 9 It should be noted that neutrophilic inflammation was not prevalent in animals in that study, which is in contrast to most other reports that have examined spinal cord or …”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…In a previous study that examined mRNA expression of cytokines in the spinal cord of dogs with IVDH-associated SCI, IL-8 was likewise found to be increased, compared to control dogs, especially in acute injury. 9 It should be noted that neutrophilic inflammation was not prevalent in animals in that study, which is in contrast to most other reports that have examined spinal cord or …”
Section: Discussioncontrasting
confidence: 52%
“…7 A small group of studies has demonstrated that inflammatory mechanisms may play a critical role in canine IVDH-associated SCI. [8][9][10][11] In particular, in acute canine SCI, resident microglial activation is prominent as is upregulation of matrix metalloproteinase 9, release of myelin basic protein, and overproduction of interleukin (IL)-6 and IL-8 messenger RNA (mRNA). [9][10][11][12] In order to further develop this model system, a broader understanding of inflammatory mechanisms after SCI is needed, particularly if pathways are to be targeted in preclinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Lipopolysaccharides induce the expression of IL-6 in canine macrophages, such as DH82 cells (Fujimoto et al 2012), blood mononuclear cells and Kupffer cells in vitro (Hamano et al 2002;Shi et al 1995). Moreover, IL-6 expression is associated with inflammation (Spitzbarth et al 2011) and macrophage infiltration into inflamed tissues in dog (Klocke et al 2005). IFNγ expression is also a result of the activation of blood mononuclear cells in the dog (Panaro et al 2001) and increases the cytotoxic activity of canine alveolar macrophages in vitro (Kurzman et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…However, shortly after the primary injury, a complex and dynamic cascade of cellular processes including inflammation, edema, ischemia, reactive species liberation, excitotoxicity, and microglial and astrocytic activation occur 11, 12, 13, 14. This spectrum of responses is known as the “secondary injury,” and it occurs seconds to weeks after the primary injury 12, 15…”
mentioning
confidence: 99%